Dual-function transaminases with hybrid nanoflower for the production of value-added chemicals from biobased levulinic acid - Khobragade, Taresh P.; Giri, Pritam; Pagar, Amol D.; Patil, Mahesh D.; Sarak, Sharad; Joo, Sangwoo; Goh, Younghwan; Jung, Seohee; Yoon, Hyunseok; Yun, Subin; Kwon, Youkyoung; Yun, Hyungdon (Frontiers in Bioengineering and Biotechnology, 2023)
The U.S. Department of Energy has listed levulinic acid (LA) as one of the top 12 compounds derived from biomass. LA has gained much attention owing to its conversion into enantiopure 4-aminopentanoic acid through an amination reaction. Herein, we developed a coupled-enzyme recyclable cascade employing two transaminases (TAs) for the synthesis of (S)-4-aminopentanoic acid. TAs were first utilized to convert LA into (S)-4-aminopentanoic acid using (S)-α-Methylbenzylamine [(S)-α-MBA] as an amino donor. The deaminated (S)-α-MBA i.e., acetophenone was recycled back using a second TAs while using isopropyl amine (IPA) amino donor to generate easily removable acetone. Enzymatic reactions were carried out using different systems, with conversions ranging from 30% to 80%. Furthermore, the hybrid nanoflowers (HNF) of the fusion protein were constructed which afforded complete biocatalytic conversion of LA to the desired (S)-4-aminopentanoic acid. The created HNF demonstrated storage stability for over a month and can be reused for up to 7 sequential cycles. A preparative scale reaction (100 mL) achieved the complete conversion with an isolated yield of 62%. Furthermore, the applicability of this recycling system was tested with different β-keto ester substrates, wherein 18%–48% of corresponding β-amino acids were synthesized. Finally, this recycling system was applied for the biosynthesis of pharmaceutical important drug sitagliptin intermediate ((R)-3-amino-4-(2,4,5-triflurophenyl) butanoic acid) with an excellent conversion 82%.